2021
DOI: 10.1109/tnnls.2020.2985720
|View full text |Cite
|
Sign up to set email alerts
|

LSTM-MSNet: Leveraging Forecasts on Sets of Related Time Series With Multiple Seasonal Patterns

Abstract: Generating forecasts for time series with multiple seasonal cycles is an important use-case for many industries nowadays. Accounting for the multi-seasonal patterns becomes necessary to generate more accurate and meaningful forecasts in these contexts. In this paper, we propose Long Short-Term Memory Multi-Seasonal Net (LSTM-MSNet), a decompositionbased, unified prediction framework to forecast time series with multiple seasonal patterns. The current state of the art in this space are typically univariate meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(66 citation statements)
references
References 45 publications
0
66
0
Order By: Relevance
“…Therefore ML models are able to extract patterns from irregular collections of time series which cannot be distinguished at individual level. Recent studies [34,[36][37][38][39] have demonstrated that Neural Networks (NNs) are particularly well suited to take advantage of a dataset which consists of large amounts of time-series. Moreover, whereas classical models are typically limited to univariate inputs, NNs are able to use multiple inputs, and therefore these types of models can be enhanced by (additional) explanatory variables.…”
Section: Forecasting Time-series Of Shoreline Positionsmentioning
confidence: 99%
“…Therefore ML models are able to extract patterns from irregular collections of time series which cannot be distinguished at individual level. Recent studies [34,[36][37][38][39] have demonstrated that Neural Networks (NNs) are particularly well suited to take advantage of a dataset which consists of large amounts of time-series. Moreover, whereas classical models are typically limited to univariate inputs, NNs are able to use multiple inputs, and therefore these types of models can be enhanced by (additional) explanatory variables.…”
Section: Forecasting Time-series Of Shoreline Positionsmentioning
confidence: 99%
“…For example, [36] proposes a hierarchical prediction method that combines the Exponential Smoothing (ES) model with the Long Short Term Memory (LSTM) neural network to extract local as well as global information from time series data. [37] proposes a model called Long Short-Term Memory Multi-Seasonal Net (LSTM-MSNet), which is able to predict the changes of time series with multiple seasonal patterns. [38] proposes a network traffic prediction model which combines STL and LSTM.…”
Section: Related Workmentioning
confidence: 99%
“…Notable techniques include Seasonal and Trend decomposition using Loess (STL) [24], which could be extended for multiple seasonalities, trigonometricbased decomposition (TBATS) [25], and Singular Spectrum Analysis (SSA) [26]. In [27], a decomposition-based LSTM model was proposed to deal with multiple seasonal patterns. In that model, the time series is decomposed into various seasonal components, which are used as exogenous regressors in an LSTM.…”
Section: Introductionmentioning
confidence: 99%